2014
DOI: 10.1016/j.bbamem.2014.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly and interactions of short antimicrobial cationic lipopeptides with membrane lipids: ITC, FTIR and molecular dynamics studies

Abstract: In this work, the self-organization and the behavior of the surfactant-like peptides in the presence of biological membrane models were studied. The studies were focused on synthetic palmitic acid-containing lipopeptides, C16-KK-NH2 (I), C16-KGK-NH2 (II) and C16-KKKK-NH2 (III). The self-assembly was explored by molecular dynamics simulations using a coarse-grained force field. The critical micellar concentration was estimated by the surface tension measurements. The thermodynamics of the peptides binding to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 33 publications
3
40
2
Order By: Relevance
“…These models are simplistic and, consequently, they have some limitations, and it is necessary to evaluate whether the selected model fits the purpose of the simulation [86]. However, these models have been used to evaluate drug-membrane interactions, such as volatile anaesthetics [89], antiparasitic drugs [90] and antimicrobial peptides [91][92][93][94][95][96][97][98]. Bereau and Kremer (2015) showed that MD simulations with coarse-grained models can lead to free energy profiles that are similar to those obtained by allatom simulations [99].…”
Section: Accepted Manuscriptmentioning
confidence: 92%
“…These models are simplistic and, consequently, they have some limitations, and it is necessary to evaluate whether the selected model fits the purpose of the simulation [86]. However, these models have been used to evaluate drug-membrane interactions, such as volatile anaesthetics [89], antiparasitic drugs [90] and antimicrobial peptides [91][92][93][94][95][96][97][98]. Bereau and Kremer (2015) showed that MD simulations with coarse-grained models can lead to free energy profiles that are similar to those obtained by allatom simulations [99].…”
Section: Accepted Manuscriptmentioning
confidence: 92%
“…The uptake and membrane interaction mechanisms of some CPPs and AMPs have been examined using experimental methods for accurate representation of cellular environments and computational methods for atomistic details, but a clear description is still missing for pVEC . Peptide translocation takes place on the order of minutes, and in addition, the cellular and membrane environment is more complex than a simple membrane model.…”
Section: Introductionmentioning
confidence: 99%
“…Lys11 in the pVEC sequence are highly conserved in VE-cadherin proteins from different organisms, suggesting that they carry functional importance for the full-length protein as well. 38 The uptake and membrane interaction mechanisms of some CPPs and AMPs have been examined using experimental methods for accurate representation of cellular environments 29,[39][40][41][42] and computational methods [43][44][45][46] for atomistic details, but a clear description is still missing for pVEC. 3 Peptide translocation takes place on the order of minutes, 47,48 and in addition, the cellular and membrane environment is more complex than a simple membrane model.…”
mentioning
confidence: 99%
“…hydrogen, van der Waals) that drive the process forward [273,274]. Computational approaches can further give an insight to the initial electrostatic interactions that govern the binding of lipopeptides to the hydrophobic core of the membrane [275]. The atomistic level of detail afforded by simulations opens the path toward the design of novel peptide analogs with increased efficacy [276].…”
Section: Computer Simulationsmentioning
confidence: 99%